Beş Faktör Kişilik Özelliklerinin Gençlik Liderliğine Etkisi: Üniversite Öğrencileri Üzerine Bir Çalışma. - ARIBAŞ, Ayşe Nihan; OĞUZ, Yavuz Sezer (Afyon Kocatepe University Journal of Social Sciences / Afyon Kocatepe Üniversitesi Sosyal Bilimler Dergisi, 2023)
In this context, in this study, it's aimed to determine the effects of university students' 5-factor personality traits on youth leadership traits were tried to be determined. For this purpose, an empirical research was conducted on university students. Questionnaire technique, which is one of the quantitative data collection techniques, was used in the research. The data obtained from the sample were analyzed with the SPSS (Statistical Package for Social Sciences) package program. This research was conducted to determine the effect of university students' five-factor personality traits on youth leadership characteristics. The sample of the study consists of 405 people. In addition, demographic Information Form, 5 Factor Personality Traits Scale and Youth Leadership Traits Scale were used as data collection tools in the research. According to the results of the research, it has been revealed that there is a positive and significant relationship between the 5-factor personality traits and the youth leadership traits. According to the results of the regression analysis, it was revealed that the 5-factor personality traits of extraversion, agreeableness and openness to experience have a positive and significant effect on youth leadership. Since this research was conducted with a quantitative method with a questionnaire, it is thought that other researchers will contribute to the literature with different methods or applications. In this context, the research is considered important in terms of setting an example.